Bioaugmentation of PAH-Contaminated Soils With Novel Specific Degrader Strains Isolated From a Contaminated Industrial Site. Effect of Hydroxypropyl-β-Cyclodextrin as PAH Bioavailability Enhancer - Villaverde, Jaime; Láiz, Leonila; Lara-Moreno, Alba; González-Pimentel, J. L.; Morillo, Esmeralda (Frontiers in Microbiology, 2019)
A PAHs-contaminated industrial soil was analysed using PCR amplification of the gene 16S ribosomal RNA for the detection and identification of different isolated bacterial strains potentially capable of degrading PAHs. Novel degrader strains were isolated and identified as Achromobacter xylosoxidans 2BC8 and Stenotrophomonas maltophilia JR62, which were able to degrade PYR in solution, achieving a mineralisation rate of about 1.00 % days-1. A. xylosoxidans was also able to mineralise PYR in slurry systems using three selected soils, and the total extent of mineralisation (once a plateau was reached) increased 4.5%, 21% and 57.5% for soils LT, TM and CR, respectively, regarding the mineralisation observed in the absence of the bacterial degrader. Soil TM contaminated with PYR was aged for 80 days and total extent of mineralization was reduced (from 46% to 35% after 180 days), and the acclimation period increased (from 49 to 79 days). Hydroxypropyl-ß-cyclodextrin (HPBCD) was used as a bioavailability enhancer of PYR in this aged soil, provoking a significant decrease in the acclimation period (from 79 to 54 days) due to an increase in PYR bioavailable fraction just from the beginning of the assay. However, a similar global extension of mineralisation was obtained. A. xylosoxidans was then added together with HPBCD to this aged TM soil contaminated with PYR, and the total extent of mineralisation decreased to 25% after 180 days, possibly due to the competitive effect of endogenous microbiota and the higher concentration of PYR in the soil solution provoked by the addition of HPBCD, which could have a toxic effect on the A. xylosoxidans strain.